ELECTRICALLY DRIVEN ROTARY VOLUMETRIC PUMP EFFICIENCY (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
This paper presents the development and experimental validation of a rotary volumetric pump with profiled rotors designed for domestic water supply systems. The proposed solution integrates an electric drive system coupled with frequency control to improve hydraulic and energy performance. A constructive concept, mathematical modeling, and an experimental prototype were developed at the National University of Science and Technology POLITEHNICA of Bucharest. Comparative studies with conventional centrifugal pumps highlight significant improvements in energy efficiency, lower power demand, and the ability to convey viscous fluids or suspensions without performance degradation. Experimental installations equipped with sensors and monitoring instruments confirmed theoretical predictions, demonstrating that integrating electrically driven rotary volumetric pumps can reduce operational energy consumption and increase reliability in civil building services. These results underline the potential contribution of the proposed pump to sustainable energy management in water distribution systems.
Keywords: Rotary volumetric pump; Profiled rotors; Electrical drive; Frequency control; Energy efficiency; Building water supply systems